A qualitative research: Self-compassion of women in early adulthood with atopic dermatitis since early childhood - Angela, Janessa; Lentari, Fransisca Rosa Mira (Universitas Mercu Buana Yogyakarta, 2023)
Atopic dermatitis (AD) is a chronic skin disease that generally appears from infancy to adulthood and is more common in women. People with AD may experience physical, psychological, and social impacts that disrupt their everyday lives. Those impacts may affect their quality of life, hence people with AD need self-compassion to face their condition. Self-compassion has its negative and positive components, uncompassionate and compassionate response. This research aims to understand self-compassion of women in early adulthood with AD since toddlers. Descriptive phenomenology is used as a research method. Results showed that self-compassion tends to be dynamic in each of the participants. Participants were more likely to show uncompassionate responses when their AD relapses, while compassionate responses were shown when they have better skin condition. Self-compassion was found to help participants in accepting and giving love to themselves when facing various conditions, so that they function better in their daily lives. Future research could delve more into the impact of family’s experience to one’s self-compassion. Support systems can be helpful for individuals with AD to share their sufferings.